Microsurgical Resection of Suprasellar Craniopharyngioma—Technical Purview - Nanda, Anil; Narayan, Vinayak; Mohammed, Nasser; Savardekar, Amey R.; Patra, Devi Prasad (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives Complete surgical resection is an important prognostic factor for recurrence and is the best management for craniopharyngioma. This operative video demonstrates the technical nuances in achieving complete resection of a suprasellar craniopharyngioma.Design and Setting The surgery was performed in a middle-aged lady who presented with the history of progressive bitemporal hemianopia and excessive sleepiness over 8 months. On imaging, suprasellar craniopharyngioma was identified. The tumor was approached through opticocarotid cistern and lamina terminalis. Exposure of bilateral optic nerves, right internal carotid artery, anterior cerebral artery, and its perforator branches was then afforded and the tumor was gross totally resected.Results The author demonstrates step-by-step technique of microsurgical resection of suprasellar craniopharyngioma. The narrow corridor to deeper structures, intricacies of multiple perforator vessels, and the technique of arachnoid and capsule dissection are the main challenging factors for the gross total resection of craniopharyngioma. The tumor portion which lies under the ipsilateral optic nerve is a blind spot region with a high chance of leaving residual tumor. Mobilization of optic nerve may endanger visual function too. The use of handheld mirror [‘mirror-technique’] helps in better visualization of this blind spot and achieve complete excision.Conclusions The technical pearls of craniopharyngioma surgery include the optimum utilization of translamina terminalis route, wide opening of the cisterns, meticulous separation of deep perforator vessels, capsular mobilization/traction avoidance, and the use of “mirror-technique” for blind-spot visualization. These surgical strategies help to achieve complete resection without causing neurological deficit.The link to the video can be found at: https://youtu.be/9wHJ4AUpG50.
Keywords: craniopharyngioma; suprasellar; resection; mirror-technique